Ultra‐Low Current 10 nm Spin Hall Nano‐Oscillators - Behera, Nilamani; Chaurasiya, Avinash Kumar; González, Victor H.; Litvinenko, Artem; Bainsla, Lakhan; Kumar, Akash; Khymyn, Roman; Awad, Ahmad A.; Fulara, Himanshu; Åkerman, Johan (Advanced Materials, 2024)
Nano‐constriction based spin Hall nano‐oscillators (SHNOs) are at the forefront of spintronics research for emerging technological applications, such as oscillator‐based neuromorphic computing and Ising Machines. However, their miniaturization to the sub‐50 nm width regime results in poor scaling of the threshold current. Here, it shows that current shunting through the Si substrate is the origin of this problem and studies how different seed layers can mitigate it. It finds that an ultra‐thin Al2O3 seed layer and SiN (200 nm) coated p‐Si substrates provide the best improvement, enabling us to scale down the SHNO width to a truly nanoscopic dimension of 10 nm, operating at threshold currents below 30 μ$\umu$A. In addition, the combination of electrical insulation and high thermal conductivity of the Al2O3 seed will offer the best conditions for large SHNO arrays, avoiding any significant temperature gradients within the array. The state‐of‐the‐art ultra‐low operational current SHNOs hence pave an energy‐efficient route to scale oscillator‐based computing to large dynamical neural networks of linear chains or 2D arrays. Spin Hall nano‐oscillators as narrow as 10 nm, with auto‐oscillation threshold currents below 30 μ$\umu$A, are experimentally demonstrated and studied using electrical microwave measurements and optical micro‐Brillouin light scattering microscopy. The current shunting issue through the Si substrate is successfully addressed using different insulating seed layers, with ultra‐thin Al2O3 showing the best performance and SiO2 the worst.